Impact of Dietary Supplementation of Vitamins C and E on the Productive Traits, Egg Quality and Immune Response of Guinea Fowl in Al-Ahsa Province, Saudia Arabia - Abdulmohsen, M; Al-Rasheedb, MI; Shawky, M; Abdel-Raheem, SM (Journal of the Hellenic Veterinary Medical Society, 2023)
Guinea fowl production makes significant contributions to animal protein through producing cheap meat and eggs, which serve as a buffer to shortages of poultry products. This study aims to e the effect of vitamin C, vitamin E solely and together on laying performance, egg quality and some blood parameters of Guinea fowl. A total of 180 black guinea fowls at eight months of age were equally divided into four groups, 45 birds, each. Each group was subdivided into 3 replicates, each one consists of 15 birds. The dietary treatments include the control group (basal diet); basal diet plus 500 mg /kg vitamin C (T1); basal diet plus 200 mg/kg vitamin E and basal diet plus 500 mg vitamin C and 200 mg vitamin E /kg feed. The results revealed that, the overall production characters including livability of laying guinea fowl were significantly improved (P<0.05) by the dietary inclusion of vitamin C and E singly or in combinations. The hen day egg production %, egg mass, albumen height, albumen weight, egg length, egg width and egg shell thickness were higher (P < 0.01) in the group supplemented with the combination of vitamin C and E in comparison with other treatment groups. In addition, supplementation of the dietary combination of vitamin C and E significantly increased (P<0.01) the Newcastle vaccine antibody titer and blood metabolites than single supplementation of both vitamins. In conclusion, the combined dietary supplementation of 500 mg /kg vitamin C and 200 mg/kg vitamin E had proved to be successful in improving the productive performance, egg quality, immune responses and the general health of black guinea fowl under present experimental conditions. This study proposes the synergistic beneficial action between vitamin C and vitamin E when supplemented together to Guinea fowl.